2009
DOI: 10.1017/s146114570900011x
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol and another atypical opioid meperidine have exaggerated serotonin syndrome behavioural effects, but decreased analgesic effects, in genetically deficient serotonin transporter (SERT) mice

Abstract: The serotonin syndrome is a potential side effect of serotonin-enhancing drugs, including antidepressants such as selective serotonin reuptake inhibitors (SSRIs) and monoamine oxidase inhibitors (MAOIs). We recently reported a genetic mouse model for the serotonin syndrome, as serotonin transporter (SERT)-deficient mice have exaggerated serotonin syndrome behavioral responses to the MAOI tranylcypromine and the serotonin precursor 5-hydroxy-L-tryptophan (5-HTP). As numerous case reports implicate the atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 85 publications
2
21
0
4
Order By: Relevance
“…Complete loss of functional SERT caused spontaneous serotonin syndrome-like behaviors (tremor, Straub tail and backward movement) and hypersensitivity to its induction by serotonergic or opioid drugs, reduced motor coordination, strength, and locomotor activity, an anxiety-like and depressive-like phenotype and decreased aggression and other social interactions (214-227). In agreement with the large literature implicating 5-HT in the pathophysiology and treatment of mood and anxiety disorders, SERT-deficient (−/− and +/-) mice showed an anxiogenic phenotype, which was ameliorated by a 5-HT1A antagonist (215, 220, 228, 229). Cognitive assays showed SERT−/− rodents may perform better in emotionally guided/motivated learning, but worse in “neutral” tasks - perhaps related to the anxiety-like phenotype (230, 231).…”
Section: Animal Geneticssupporting
confidence: 86%
“…Complete loss of functional SERT caused spontaneous serotonin syndrome-like behaviors (tremor, Straub tail and backward movement) and hypersensitivity to its induction by serotonergic or opioid drugs, reduced motor coordination, strength, and locomotor activity, an anxiety-like and depressive-like phenotype and decreased aggression and other social interactions (214-227). In agreement with the large literature implicating 5-HT in the pathophysiology and treatment of mood and anxiety disorders, SERT-deficient (−/− and +/-) mice showed an anxiogenic phenotype, which was ameliorated by a 5-HT1A antagonist (215, 220, 228, 229). Cognitive assays showed SERT−/− rodents may perform better in emotionally guided/motivated learning, but worse in “neutral” tasks - perhaps related to the anxiety-like phenotype (230, 231).…”
Section: Animal Geneticssupporting
confidence: 86%
“…Although the spontaneous pain sensitivity is unaltered in these mutant mice compared to their wild-type littermates [221], multiple sources of evidence suggest that the pharmacological blockade of 5-HTT induced by SSRIs reduces acute pain in the hotplate and tail flick tests (Table 3). For example, citalopram produces antinociceptive effects in both rats [222-224] and mice [219,225].…”
Section: Monoamines Reuptake Inhibitors and Pain Preclinical Outcomesmentioning
confidence: 99%
“…Animals were placed in a large Plexiglass cylinder and after 15 min of habituation were administered 5-HTP (80 mg kg −1 ) 18,19 or its vehicle in the first experiment and tramadol (60 mg kg −1 ) 33 or its vehicle in the second experiment. Behavioral assessments were made based on previous methods.…”
Section: Methodsmentioning
confidence: 99%
“…31,32 We previously showed that SERT-KO mice display increased baseline levels of serotonin syndrome behaviors, 19,33,34 in addition to further exaggerated behavioral responses following the MAOA/B inhibitor tranylcypromine, 19 5-HTP 18,32,35 and the atypical opioids tramadol and meperidine, 33 each when administered alone.…”
Section: Introductionmentioning
confidence: 99%